1999
DOI: 10.21273/jashs.124.2.205
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hydraulic Characteristics of Volcanic Materials on Yield of Roses Grown in Soilless Culture

Abstract: Rose (Rosa sp.) plants (`Mercedes') were grown in yellow tuff (YT) (volcanic ash, scoria) and pumice from Italy (PI) and Greece (PG) for which physical and hydraulic characteristics were determined. The differences among the measured retention curves of these materials result in significant differences among their relative hydraulic conductivity functions. The hydraulic conductivity of YT is much higher than that of PI, which is higher than that of PG. The plants were subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 14 publications
(15 reference statements)
2
40
0
Order By: Relevance
“…This may be attributed to the capability of zeolites to increase water retention [3] and improve cation-exchange capacity [23] of the substrate. Increased water availability in the root medium may be attributed to increased unsaturated hydraulic conductivity, [25] which is enhanced in substrates with relatively high volume of water-filled pores or CC as was the case with peatmoss-perlite (Table 2). [23] This feature makes zeolites widely used as water saver and slow-release fertilizers.…”
Section: Resultsmentioning
confidence: 99%
“…This may be attributed to the capability of zeolites to increase water retention [3] and improve cation-exchange capacity [23] of the substrate. Increased water availability in the root medium may be attributed to increased unsaturated hydraulic conductivity, [25] which is enhanced in substrates with relatively high volume of water-filled pores or CC as was the case with peatmoss-perlite (Table 2). [23] This feature makes zeolites widely used as water saver and slow-release fertilizers.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Tolk () indicated a correspondence between water content at −1471.50 kPa and wilting point estimated by the sunflower method. Results clearly suggested that hydraulic conductivity was a driving factor in the wilting process (Raviv et al , ). It is probable that hydraulic conductivity decreased in large aggregates and water content at wilting point increased accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Some typical examples are listed in Table 13.1. Kemble et al, 1994;di Benedetto and Klasman, 2004 Lettuce and other leafy vegetables Long season vegetables (tomato, pepper) 9-12 months Hydroponics 1-2 l Peterson et al, 1991a Perennial cut flowers (rose) 3-5 years 5-10 l Raviv et al, 1999; Tree saplings one year Transportation required ∼5 l Salifu et al, 2006 One common practical consideration for growers that dictates the root-zone volume is the interval between irrigation events. While it would be ideal to tailor the irrigation schedule to the needs ot the plants, many growers set the irrigation schedule for convenience or to take advantage of available capacity for irrigation.…”
Section: Choosing the Appropriate Medium Root Volume And Growing Systemmentioning
confidence: 99%